Multiplexed genetic profiling of human blood platelets using fluorescent microspheres - Gnatenko, Dmitri V.; Zhu, Wei; Bahou, Wadie F. (Thrombosis and Haemostasis, 2008)
Human platelets have unique and reproducible mRNA profiles, with evidence for distinct profiles in haematopoietic stem cell disorders associated with thrombocytosis. Platelet transcript profiling is traditionally studied by microarray analysis, quantitative reverse transcription-PCR or serial analysis of gene ex-pression,techniques that are labor- and technically-intensive.We have now applied a novel multiplex-based platform for quantitative transcript profiling of human platelets.Simultaneous quantification of 17 platelet transcripts was assayed using intact platelet-rich plasma or gel-filtered platelets lysed in vitro.Accurate and reproducible profiles could be obtained from as few as 5 X 107 platelets (a platelet mass corresponding to ∼100 µl of whole blood), even for the low-abundant platelet transcripts. Correlation coefficients of this 17-member gene set to platelet Affymetrix microarrays were excellent (r2 = 0.949, p < 1 X 10–10), with no correlation to in kind-derived leukocyte profiles, highlighting the cell-specificity of the platform.These data demonstrate that transcript multiplexing using fluorescent micro-spheres can be adapted for rapid molecular profiling using intact platelets (bypassing the need for RNA isolation methods), with potential applicability irrespective of baseline platelet counts.
Keywords: Platelets; transcript profiling; fluorescent microspheres; Luminex; mRNA